Implementasi Metode Group Investigation Terhadap Peningkatan Prestasi Belajar Sejarah Kebudayaan Islam Kelas IV Madrasah Ibtidaiyah - Bagus Wicaksono (Halaqa: Islamic Education Journal, 2019)
The purpose of this study was to determine whether the implementation of the method of group investigation can improve the learning achievement of fourth grade students in semester 2 of the SKI subject in the subject of 'Mi' of the Prophet Muhammad SAW at MI . This research is a classroom action research (CAR) in which there are steps of planning, action, observation and reflection in each cycle. Data collection techniques using observation, interviews, questionnaires and documentation. The data obtained were calculated using descriptive percentage analysis techniques. The results of observations made by researchers showed an increase in student achievement. In the first cycle, the average grade of 69. Students who experienced mastery in learning are still 16 students or 50% while students who have not completed the learning process also have 16 students or 50%. In the second cycle after the improvement is made, the average grade of the class becomes 80.3. There are 24 students or 75% have been completed in learning students who have not completed the learning process there are 8 students or 25%. This shows an increase of 25%.